Persistence of socioeconomic inequalities in the knowledge of cardiovascular risk factors five years after coronary angiography. (1st February 2018) - Tchicaya, Anastase; Lorentz, Nathalie; Demarest, Stefaan; Beissel, Jean
Abstract: Background: Cardiovascular diseases are important causes of death, morbidity, and years of potential life lost in most developed countries. Aims: The purpose of this study was to assess trends in knowledge of cardiovascular risk factors among patients five years after coronary angiography and to investigate the impact of educational level on knowledge level. Methods: The study included 1289 of 4391 patients admitted for cardiac events in 2008/2009 at the National Institute for Cardiac Surgery and Interventional Cardiology, Luxembourg. A follow-up study was conducted by post five years later (2013/2014). Data were obtained from 1837 of the contacted patients (with 548 reported deaths) (response rate=42%). Logistic regression models were used to evaluate the association between educational level and knowledge of cardiovascular risk factors. Educational level was used as a surrogate for socioeconomic status. Results: In total, 39.9% of patients could list at least three risk factors in 2013/2014, a much higher percentage than the 8.5% observed during the initial survey. In both sexes, knowledge of cardiovascular risk factors increased between 2008/2009 and 2013/2014. Patients with higher educational levels were more likely (odds ratio=2.33, 95% confidence interval: 1.63–3.34) to cite at least three risk factors than patients with lower education levels. Conclusion: Knowledge level was associated with educational level, and improved for all educational groups five years after coronary angiography. Educational differences in knowledge persisted, but the gaps decreased. Improving knowledge of cardiovascular risk factors among patients with cardiovascular disease will help increase awareness and promote lifestyle changes.